Fine-grain dielectric material for high-voltage and high-reliability mlcc and preparation method thereof
Patent Information
- Application Number
- CN202611189039.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]为了克服上述的技术问题,本发明的目的在于提供一种高压高可靠性MLCC用细晶介质材料及其制备方法,解决了现有的MLCC用细晶介质材料在高温高电场下晶界稳定性差、添加剂分散不均的问题
本发明的一种高压高可靠性MLCC用细晶介质材料及其制备方法,通过将钛酸钡粉体、锆酸钙、高熵烧绿石纳米晶、多层核壳纳米功能单元以及黏结剂混合球磨,过筛,真空脱泡,注入流延机中流延,得到陶瓷膜片;将膜片裁切,通过丝网印刷在膜片表面印制镍内电极浆料,进行叠层对齐堆叠,上下覆盖陶瓷保护膜片,压制得到多层陶瓷生坯;将多层陶瓷生坯置于承烧板上,升温排胶,取出排胶坯体,置于气氛隧道炉的推进舟皿上烧结,切换气氛进行再氧化热处理,冷却,得到高压高可靠性MLCC用细晶介质材料;通过高熵烧绿石纳米晶与径向梯度多层核壳纳米功能单元的协同作用,构建了静态钉扎、可编程时序烧结以及主动应力缓冲的细晶界网络;该材料晶粒细小且尺寸分布均一,单位厚度内密集的晶界网络有效分担了外加电场,避免了局部电场集中引发的提前击穿;内层SiO2点阵衍生的弥散纳米闭气孔作为应力缓冲中心,主动吸收电致伸缩与热循环产生的内应力,抑制微裂纹的萌生与扩展,赋予材料优异的击穿耐受能力与抗疲劳长寿命特性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic ceramic materials technology, specifically to a fine-grained dielectric material for high-voltage, high-reliability MLCCs and its preparation method. Background Technology
[0002] Multilayer ceramic capacitors (MLCCs) are indispensable basic components in electronic devices, widely used in consumer electronics, automotive electronics, industrial power supplies, and aerospace. With the rapid development of electronic devices towards miniaturization, high frequency, and high power density, especially the popularization of high-voltage platforms for electric vehicles and industrial-grade gallium nitride fast charging technology, the market has placed extremely stringent requirements on the rated voltage, safety, reliability, and environmental adaptability of MLCCs. To meet these requirements, the mainstream technical approach is to use barium titanate as the matrix and form a fine-grained dielectric material with a "core-shell" structure by doping with rare earth oxides, in order to achieve a stable dielectric constant, high breakdown field strength, and long service life over a wide temperature range.
[0003] However, traditional doping modification schemes rely on the pinning effect of single acceptor and donor ions at grain boundaries to suppress grain growth. This simple grain boundary phase is not stable enough under high temperature and high electric field, and is prone to unpinning, leading to abnormal grain growth and deterioration of breakdown field strength and insulation resistance. In terms of additive uniformity, traditional solid-state ball milling mixing process is difficult to achieve molecular-level uniform dispersion of multiple additives on barium titanate matrix, often resulting in local component segregation. This segregation can cause non-uniform liquid phase and grain growth during sintering, resulting in microstructure inhomogeneity, and in turn, internal stress concentration and electric field distortion.
[0004] Therefore, the fine-grained dielectric material for high-voltage, high-reliability MLCCs and its preparation method of the present invention are of great significance in the field of electronic ceramic materials technology. Summary of the Invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a fine-grained dielectric material for high-voltage and high-reliability MLCCs and its preparation method, which solves the problems of poor grain boundary stability and uneven additive dispersion of existing fine-grained dielectric materials for MLCCs under high temperature and high electric field.
[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a fine-grained dielectric material for high-voltage, high-reliability MLCCs, comprising the following components by weight: 95-100 parts of barium titanate powder, 2-4 parts of calcium zirconate, 0.1-0.5 parts of high-entropy pyrochlore nanocrystals, 0.5-2 parts of multilayer core-shell nanofunctional units, and 8-12 parts of binder; The barium titanate powder is prepared by a hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98.
[0007] In a preferred embodiment of the present invention, the high-entropy pyrochlore nanocrystals are prepared by the following steps: Lanthanum nitrate hexahydrate, neodymium nitrate hexahydrate, samarium nitrate hexahydrate, europium nitrate hexahydrate, gadolinium nitrate hexahydrate, zirconium oxynitrate, and ultrapure water were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was stirred for 30 minutes to obtain a mixed salt solution. Under ultrasonic assistance at 40-80 kHz, the mixed salt solution was sprayed into an ammonia solution at 50-70°C at a rate of 2-5 mL / min. The mixture was stirred at 300-500 rpm to induce explosive co-precipitation, forming a mixed hydroxide colloid. This colloid was then transferred to a high-pressure reactor and heated to 180-220°C. Static hydrothermal treatment was performed in an oven at ℃ for 12-36 h to obtain pyrochlore phase nanocrystal nuclei. These nuclei were then washed 2-3 times each with distilled water and anhydrous ethanol in a centrifuge at 8000 r / min. The nuclei were then freeze-dried in a vacuum freeze dryer at -50℃ for 24 h to obtain precursor powder. The precursor powder was spread evenly in a crucible and placed in a tube furnace. Pure oxygen was introduced at a flow rate of 100-200 mL / min, and the furnace was flash-calcined at a rate of 80-120℃ / min to 750-850℃. The furnace was held at this temperature for 1-5 min and then cooled to 25℃ to obtain high-entropy pyrochlore nanocrystals.
[0008] In a preferred embodiment of the present invention, the ratio of the amounts of lanthanum nitrate hexahydrate, neodymium nitrate hexahydrate, samarium nitrate hexahydrate, europium nitrate hexahydrate, gadolinium nitrate hexahydrate, zirconium oxynitrate, ultrapure water, and ammonia solution is 4.3-4.35g: 4.35-4.4g: 4.4-4.45g: 4.45-4.5g: 4.5-4.55g: 2.3-2.5g: 200mL: 500mL; and the mass fraction of the ammonia solution is 25-28%.
[0009] In a preferred embodiment of the present invention, the multilayer core-shell nanofunctional unit is prepared by the following steps: Step b1: Add barium titanate powder and the first portion of deionized water to a three-necked flask equipped with a stirrer and thermometer. Sonicate the mixture for 30 min at 300 W and 40 kHz to obtain a suspension slurry. Add polydiallyldimethylammonium chloride aqueous solution while stirring at 400 r / min. Stir and adsorb the mixture in a 25 °C constant temperature water bath for 1 h. After the reaction is complete, centrifuge at 8000 r / min for 5 min, discard the supernatant, wash the precipitate 2-3 times with distilled water, add the second portion of deionized water, mix and stir for 15-20 min, transfer to a jacketed glass reactor, add tetraethyl orthosilicate ethanol solution dropwise at 0.5 mL / min in a 40 °C water bath, adjust the pH to 9.5 with ammonia, stir and react at 200 r / min for 4-5 h, centrifuge at 8000 r / min for 5 min, wash the precipitate 2-3 times with distilled water and anhydrous ethanol respectively to obtain the intermediate product. Step b2: Mix the intermediate product and deionized water and sonicate for 15 min. Add magnesium acetate tetrahydrate and manganese acetate trihydrate. Mix and stir for 30 min under constant temperature water bath at 25℃ and ultrasonic assistance. Add ammonium oxalate aqueous solution dropwise at a rate of 1 mL / min under mechanical stirring at 300 r / min. Adjust the pH to 5.5-6 with acetic acid and continue stirring for 2 h. After the reaction is complete, centrifuge at 8000 r / min for 5 min. Wash the precipitate 2-3 times with distilled water and dry in a vacuum drying oven at 80℃ for 12 h to obtain Mg-Mn oxalate coated precursor. Step b3: Mix dysprosium nitrate pentahydrate, holmium nitrate pentahydrate, aluminum nitrate nonahydrate, and anhydrous ethanol and stir for 30 min. Add tetraethyl orthosilicate and continue stirring for 30 min to obtain the coating solution. Mix the Mg-Mn oxalate-coated precursor and coating solution and ultrasonically disperse for 30 min. Transfer the mixture to a constant temperature water bath reactor. Under mechanical stirring at 50℃ and 300 r / min, add the hydrolysate dropwise at a rate of 0.3 mL / min and stir for 6 h until the reaction is complete. The precipitate was then centrifuged at 8000 r / min for 5 min, washed 2-3 times with distilled water, and dried in a vacuum drying oven at 80℃ for 12 h to obtain a full-shell precursor. The full-shell precursor was spread in a crucible, transferred to a high-temperature tube furnace, and oxygen was introduced at a flow rate of 150 mL / min. The temperature was increased to 650℃ at a rate of 2℃ / min and calcined at a constant temperature for 3 h. Then, the temperature was decreased to 25℃ at a rate of 5℃ / min and removed to obtain a multilayer core-shell nanofunctional unit.
[0010] In a preferred embodiment of the present invention, the ratio of barium titanate powder, total deionized water, polydiallyl dimethyl ammonium chloride aqueous solution, and tetraethyl orthosilicate ethanol solution in step b1 is 90-100g:1500mL:40-50mL:15-20mL; the barium titanate powder is prepared by a hydrothermal method; the first part of deionized water accounts for 2 / 3 of the total deionized water; the second part of deionized water accounts for 1 / 3 of the total deionized water; the polydiallyl dimethyl ammonium chloride aqueous solution is manufactured by Merck, catalog number 409030; the concentration of the tetraethyl orthosilicate ethanol solution is 1mol / L; and the concentration of the ammonia water is 2mol / L.
[0011] In a preferred embodiment of the present invention, the ratio of the intermediate product, deionized water, magnesium acetate tetrahydrate, manganese acetate trihydrate, and ammonium oxalate aqueous solution in step b2 is 90-100g:500mL:6-7g:1-2g:100mL; the concentration of the ammonium oxalate aqueous solution is 0.1mol / L; and the concentration of the acetic acid is 1mol / L.
[0012] In a preferred embodiment of the present invention, the ratio of dysprosium nitrate pentahydrate, holmium nitrate pentahydrate, aluminum nitrate nonahydrate, anhydrous ethanol, tetraethyl orthosilicate, Mg-Mn oxalate-coated precursor, and hydrolysate in step b3 is 4-5g:4-5g:2-3g:200mL:2-2.2g:100g:50mL; the hydrolysate is an ethanol solution with a mass fraction of 80%.
[0013] Secondly, this application provides a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, comprising the following steps: Step 1: Weigh out 95-100 parts of barium titanate powder, 2-4 parts of calcium zirconate, 0.1-0.5 parts of high-entropy pyrochlore nanocrystals, 0.5-2 parts of multilayer core-shell nanofunctional units, 8-12 parts of binder, 25-35 parts of ethanol, and 25-35 parts of toluene according to the following weight proportions. Step 2: Add barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, multilayer core-shell nanofunctional units, and binder sequentially into a horizontal ball mill jar. Add ethanol and toluene, with a ball-to-material ratio of 3-5:1. After sealing the jar, place it on a horizontal ball mill and ball mill at 60-80 r / min for 24-36 h. Sieve through a 200-mesh sieve and degas in a vacuum degassing machine for 30 min. Inject into a casting machine, adjust the doctor blade gap to 50-200 μm, and cast at a casting speed of 0.5-1.5 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. Cut the film, screen print nickel internal electrode paste onto the film surface, stack and align the layers, cover with ceramic protective films on the top and bottom, pack into a vacuum-sealed bag, and press at 70℃ and 30 MPa for 15 min to obtain a multilayer ceramic green body. Step 3: Place the multi-layer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under air atmosphere, heat to 200℃ at a rate of 0.5℃ / min and hold for 1 hour, then continue heating to 350℃ and hold for 1 hour, then continue heating to 450℃ and hold for 1 hour, finally heating to 600℃ and holding for 2 hours to remove the binder. Cool to 25℃ at a rate of 2℃ / min, remove the binder-removed green body, and place it on a propeller boat in an atmosphere tunnel furnace. Infuse the furnace with a flow rate of 500-1000 mL / m. The process involves creating a weak reducing atmosphere by mixing nitrogen and hydrogen in a volume ratio of 97:3 and adjusting the oxygen partial pressure using a humidifier at 25-35℃. The temperature is then increased to 1150-1220℃ at a rate of 2-5℃ / min and held for 2-4 hours. The atmosphere is then switched to a weak oxidizing atmosphere by mixing nitrogen and oxygen in a volume ratio of 99:1. The furnace is then cooled to 900℃ and held for 2 hours for re-oxidation heat treatment. Finally, the furnace is cooled to 25℃ to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0014] The beneficial effects of this invention are: This invention discloses a fine-grained dielectric material for high-voltage, high-reliability MLCCs and its preparation method. The method involves mixing barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, multilayer core-shell nanofunctional units, and a binder, ball milling, sieving, vacuum degassing, and casting in a casting machine to obtain a ceramic diaphragm. The diaphragm is then cut, and a nickel internal electrode paste is screen-printed onto its surface. The diaphragms are then stacked and aligned, covered with top and bottom ceramic protective films, and pressed to obtain a multilayer ceramic green body. The multilayer ceramic green body is placed on a firing plate, heated to remove the binder, removed, and sintered on a propeller in an atmosphere tunnel furnace. The atmosphere is then switched for re-oxidation heat treatment, followed by cooling to obtain the final product. A fine-grained dielectric material for high-voltage, high-reliability MLCCs; through the synergistic effect of high-entropy pyrochlore nanocrystals and radially gradient multilayer core-shell nanofunctional units, a fine grain boundary network with static pinning, programmable time-sequential sintering, and active stress buffering is constructed; the material has small and uniform grain size distribution, and the dense grain boundary network per unit thickness effectively distributes the applied electric field, avoiding premature breakdown caused by local electric field concentration; the dispersed nanopores derived from the inner SiO2 lattice act as stress buffer centers, actively absorbing the internal stress generated by electrostriction and thermal cycling, inhibiting the initiation and propagation of microcracks, and endowing the material with excellent breakdown resistance and fatigue resistance and long life characteristics.
[0015] In the preparation of fine-grained dielectric materials for high-voltage, high-reliability MLCCs, high-entropy pyrochlore nanocrystals were first prepared. Five rare-earth nitrates and zirconium oxynitrate underwent explosive co-precipitation in an alkaline ammonia solution to form a mixed hydroxide colloid. Under high-temperature, high-pressure hydrothermal conditions, the hydroxides underwent dehydration condensation reactions and completed ordered rearrangement, transforming in situ into well-crystallized pyrochlore phase nanocrystal nuclei. Then, rapid heating and cooling were used to allow the nuclei to complete phase formation and densification before significant sintering and growth, resulting in high-entropy pyrochlore nanocrystals. These high-entropy pyrochlore nanocrystals act as grain boundary pinning phases, with the equimolar occupancy of the five rare-earth ions inducing lattice distortion, forming high configurational entropy. The pyrochlore effect endows it with a high grain boundary diffusion barrier, preventing coarsening or solid solution at the MLCC sintering temperature, forming pinning points, and inhibiting abnormal grain growth. At the same time, the inherent ordered oxygen vacancies in the pyrochlore structure can act as sacrificial traps, preferentially capturing and freezing oxygen vacancies migrating from the dielectric layer, blocking their long-range transport paths, reducing high-temperature leakage current, and delaying insulation resistance degradation. The flash sintering process fixes high configuration entropy and severe lattice distortion within fine grains, giving them high surface energy and chemical activity. In the early stages of sintering, a small amount of rare earth ions can diffuse to the grain surface, providing shallow donor doping, optimizing the grain boundary barrier height, and improving dielectric stability and reliability.
[0016] In the preparation of fine-grained dielectric materials for high-voltage, high-reliability MLCCs, multilayer core-shell nanofunctional units were first fabricated. The electrostatic self-assembly of the cationic polyelectrolyte polydiallyldimethylammonium chloride on the surface of barium titanate particles reversed the surface charge from negative to positive. Subsequently, tetraethyl orthosilicate was added dropwise, undergoing a controlled hydrolysis-condensation reaction under alkaline conditions. The generated SiO2 selectively deposited on the interstitial sites not occupied by polydiallyldimethylammonium chloride, forming a discrete nanolattice. This lattice then reacts with oxalate ions and adsorbed Mg... 2+ Mn 2+ A precipitation reaction occurs, forming a continuous and dense oxalate coating layer on the surface of barium titanate within the SiO2 lattice interstices; using the sol-gel method, tetraethyl orthosilicate in a solution containing Dy 3+ Ho 3+ And Al 3+ In solution, it undergoes hydrolysis and condensation, forming an amorphous rare earth silicate shell together with rare earth and aluminum ions; during the calcination stage, magnesium oxalate and manganese oxalate decompose thermally and react at the grain boundaries with Mg. 2+ and Mn 2+ / Mn 3+ Acceptor doped ions are pinned to the surface of barium titanate grains, and the amorphous shell becomes densified but not crystallized. Because the temperature is lower than the sintering temperature of barium titanate and the interlayer interdiffusion threshold, the structure of each gradient layer is locked, resulting in a multilayer core-shell nanofunctional unit. The outer amorphous rare earth silicate shell of this multilayer core-shell nanofunctional unit melts first at high temperature to form a transient liquid phase, which promotes densification of the preform before grain growth begins, achieving densification first and then controlling crystal growth, avoiding abnormal grain growth in traditional liquid phase sintering. The middle layer Mg-Mn acceptor oxide is uniformly dissolved to the grain boundaries above 1100℃, eliminating the traditional mechanical... The mechanically mixed composition segregation establishes a highly uniform acceptor pinning barrier at the grain boundaries, inhibiting oxygen vacancy migration and improving insulation resistance. After sintering, the inner SiO2 nanolattice transforms into dispersed nanopores at the grain boundaries. When the ceramic body is subjected to repeated electrostriction or thermal cycling stress, the closed pores can act as stress buffer centers, absorbing and dissipating energy, effectively preventing the initiation and propagation of microcracks, and improving breakdown field strength and cycle reliability. Rare earth ions in the shell diffuse in trace amounts to the surface of barium titanate grains during sintering, forming shallow donor doping, optimizing the height of the grain boundary Schottky barrier, and thus improving dielectric stability. Detailed Implementation
[0017] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] Example 1: This embodiment describes a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, including the following steps: Step S1: Add 4.3g lanthanum nitrate hexahydrate, 4.35g neodymium nitrate hexahydrate, 4.4g samarium nitrate hexahydrate, 4.45g europium nitrate hexahydrate, 4.5g gadolinium nitrate hexahydrate, 2.3g zirconium oxynitrate, and 200mL ultrapure water to a three-necked flask equipped with a stirrer and thermometer. Mix and stir for 30min to obtain a mixed salt solution. Under the assistance of 40kHz ultrasound, spray the mixed salt solution at a rate of 2mL / min into 500mL of ammonia solution at 50℃ and a mass fraction of 25%. Stir at 300r / min to induce explosive co-precipitation. The precipitate was precipitated to form a mixed hydroxide colloid, which was transferred to a high-pressure reactor and statically hydrothermally treated in an oven at 180°C for 12 h to obtain pyrochlore phase nanocrystal nuclei. The nuclei were washed twice each with distilled water and anhydrous ethanol in a centrifuge at 8000 r / min, and then freeze-dried in a vacuum freeze dryer at -50°C for 24 h to obtain precursor powder. The precursor powder was spread evenly in a crucible, placed in a tube furnace, and pure oxygen was introduced at a flow rate of 100 mL / min. The furnace was flash-calcined to 750°C at a rate of 80°C / min, held for 1 min, and then cooled to 25°C to obtain high-entropy pyrochlore nanocrystals. Step S2: Add 90g of barium titanate powder and 1000mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Disperse the powder ultrasonically at 300W and 40kHz for 30min to obtain a suspension. Add 40mL of polydiallyldimethylammonium chloride aqueous solution while stirring at 400r / min. Stir and react in a 25℃ constant temperature water bath for 1h. After the reaction is complete, centrifuge at 8000r / min for 5min, discard the supernatant, wash the precipitate twice with distilled water, add 500mL of deionized water, and mix... The mixture was stirred for 15 min and transferred to a jacketed glass reactor. 15 mL of a 1 mol / L tetraethyl orthosilicate ethanol solution was added dropwise at a rate of 0.5 mL / min under a 40°C water bath. The pH was adjusted to 9.5 with 2 mol / L ammonia solution. The mixture was stirred at 200 rpm for 4 h and then centrifuged at 8000 rpm for 5 min. The precipitate was washed twice each with distilled water and anhydrous ethanol to obtain the intermediate product. The polydiallyl dimethyl ammonium chloride aqueous solution was manufactured by Merck, catalog number 409030. Step S3: Mix 90g of intermediate product and 500mL of deionized water and sonicate for 15min. Add 6g of magnesium acetate tetrahydrate and 1g of manganese acetate trihydrate. Mix and stir for 30min under constant temperature water bath at 25℃ and ultrasonic assistance. Add 100mL of 0.1mol / L ammonium oxalate aqueous solution dropwise at a rate of 1mL / min under mechanical stirring at 300r / min. Adjust the pH to 5.5 with 1mol / L acetic acid. Continue stirring and react for 2h. After the reaction is complete, centrifuge at 8000r / min for 5min. Wash the precipitate twice with distilled water and dry in a vacuum drying oven at 80℃ for 12h to obtain Mg-Mn oxalate coated precursor. Step S4: Mix 4g of dysprosium nitrate pentahydrate, 4g of holmium nitrate pentahydrate, 2g of aluminum nitrate nonahydrate, and 200mL of anhydrous ethanol and stir for 30min. Add 2g of tetraethyl orthosilicate and continue stirring for 30min to obtain the coating solution; add 100g of... The Mg-Mn oxalate-coated precursor and coating solution were mixed and ultrasonically dispersed for 30 min, then transferred to a constant temperature water bath reactor. Under mechanical stirring at 50℃ and 300 r / min, 50 mL of 80% ethanol solution was added dropwise at a rate of 0.3 mL / min. The reaction was stirred for 6 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 5 min. The precipitate was washed twice with distilled water and dried in a vacuum drying oven at 80℃ for 12 h to obtain a full-shell precursor. The full-shell precursor was spread evenly in a crucible and transferred to a high-temperature tube furnace. Oxygen was introduced at a flow rate of 150 mL / min, and the temperature was increased to 650℃ at a rate of 2℃ / min. The mixture was calcined at a constant temperature for 3 h, and then cooled to 25℃ at a rate of 5℃ / min. The resulting multilayer core-shell nanofunctional unit was obtained. Step S5: Weigh out 95 parts by weight of barium titanate powder, 2 parts by weight of calcium zirconate, 0.1 parts by weight of high-entropy pyrochlore nanocrystals, 0.5 parts by weight of multilayer core-shell nanofunctional units, 8 parts by weight of binder, 25 parts by weight of ethanol, and 25 parts by weight of toluene; the barium titanate powder is prepared by hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98; Step S6: Barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, multilayer core-shell nanofunctional units, and binder are sequentially added to a horizontal ball mill jar. Ethanol and toluene are added, and the ball-to-material ratio is 3:1. After sealing the jar, it is placed on a horizontal ball mill and ball-milled at 60 r / min for 24 h. After sieving through a 200-mesh sieve, it is degassed in a vacuum degassing machine for 30 min and injected into a casting machine. The doctor blade gap is adjusted to 50 μm, and casting is performed at a casting speed of 0.5 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. The film is cut, and nickel internal electrode paste is printed on the surface of the film by screen printing. The layers are stacked and aligned, covered with ceramic protective films on the top and bottom, and then placed in a vacuum-sealed bag and pressed at 70℃ and 30 MPa for 15 min to obtain a multilayer ceramic green body. Step S7: Place the multilayer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under an air atmosphere, heat it to 200℃ at a rate of 0.5℃ / min and hold for 1 hour. Continue heating to 350℃ and hold for 1 hour. Continue heating to 450℃ and hold for 1 hour. Finally, heat it to 600℃ and hold for 2 hours to remove the binder. Cool it down to 25℃ at a rate of 2℃ / min, take out the removed green body, and place it on the propeller boat of the atmosphere tunnel furnace. Introduce a weak reducing atmosphere with a flow rate of 500mL / min, which is a mixture of nitrogen and hydrogen in a volume ratio of 97:3 and the oxygen partial pressure is adjusted by bubbling with a humidifier at 25℃. Heat it up to 1150℃ at a rate of 2℃ / min and hold for 2 hours. Switch the atmosphere to a weak oxidizing atmosphere, which is a mixture of nitrogen and oxygen in a volume ratio of 99:1. Cool it down to 900℃ with the furnace and hold for 2 hours for re-oxidation heat treatment. Cool it down to 25℃ with the furnace to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0019] Example 2: This embodiment describes a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, including the following steps: Step S1: Add 4.33g lanthanum nitrate hexahydrate, 4.38g neodymium nitrate hexahydrate, 4.43g samarium nitrate hexahydrate, 4.48g europium nitrate hexahydrate, 4.53g gadolinium nitrate hexahydrate, 2.4g zirconium oxynitrate, and 200mL ultrapure water to a three-necked flask equipped with a stirrer and thermometer. Mix and stir for 30min to obtain a mixed salt solution. Under the assistance of 60kHz ultrasound, spray the mixed salt solution at a rate of 4mL / min into 500mL of ammonia solution at 60℃ and a mass fraction of 27%. Stir at 400r / min to generate explosive co-excitation. Precipitation was generated to form a mixed hydroxide colloid, which was transferred to a high-pressure reactor and statically hydrothermally treated in an oven at 200℃ for 24 h to obtain pyrochlore phase nanocrystal nuclei. The nuclei were washed three times each with distilled water and anhydrous ethanol in a centrifuge at 8000 r / min, and then freeze-dried in a vacuum freeze dryer at -50℃ for 24 h to obtain precursor powder. The precursor powder was spread evenly in a crucible, placed in a tube furnace, and pure oxygen was introduced at a flow rate of 150 mL / min. The furnace was flash-calcined to 800℃ at a rate of 100℃ / min, held for 3 min, and then cooled to 25℃ to obtain high-entropy pyrochlore nanocrystals. Step S2: Add 95g of barium titanate powder and 1000mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Disperse the powder ultrasonically at 300W and 40kHz for 30min to obtain a suspension. Add 45mL of polydiallyldimethylammonium chloride aqueous solution while stirring at 400r / min. Stir and react in a 25℃ constant temperature water bath for 1h. After the reaction is complete, centrifuge at 8000r / min for 5min, discard the supernatant, wash the precipitate three times with distilled water, add 500mL of deionized water, and mix. Stir for 18 min, transfer to a jacketed glass reactor, and add 18 mL of 1 mol / L tetraethyl orthosilicate ethanol solution dropwise at a rate of 0.5 mL / min in a 40°C water bath. Adjust the pH to 9.5 with 2 mol / L ammonia solution, stir the reaction at 200 r / min for 4.5 h, centrifuge at 8000 r / min for 5 min, and wash the precipitate three times each with distilled water and anhydrous ethanol to obtain the intermediate product. The polydiallyl dimethyl ammonium chloride aqueous solution was manufactured by Merck, catalog number 409030. Step S3: Mix 95g of intermediate product and 500mL of deionized water and sonicate for 15min. Add 6.5g of magnesium acetate tetrahydrate and 1.5g of manganese acetate trihydrate. Mix and stir for 30min in a constant temperature water bath at 25℃ with ultrasonic assistance. Add 100mL of 0.1mol / L ammonium oxalate aqueous solution dropwise at a rate of 1mL / min under mechanical stirring at 300r / min. Adjust the pH to 6 with 1mol / L acetic acid and continue stirring for 2h. After the reaction is complete, centrifuge at 8000r / min for 5min. Wash the precipitate three times with distilled water and dry in a vacuum drying oven at 80℃ for 12h to obtain the Mg-Mn oxalate coated precursor. Step S4: Mix 4.5g of dysprosium nitrate pentahydrate, 4.5g of holmium nitrate pentahydrate, 2.5g of aluminum nitrate nonahydrate, and 200mL of anhydrous ethanol and stir for 30min. Add 2.1g of tetraethyl orthosilicate and continue stirring for 30min to obtain the coating solution. Mix 100g of Mg-Mn oxalate-coated precursor and coating solution and ultrasonically disperse for 30min. Transfer to a constant temperature water bath reactor. Under mechanical stirring at 50℃ and 300r / min, add 50mL of a mixture containing Mg-Mn oxalate at a rate of 0.3mL / min. An 80% ethanol solution was stirred for 6 hours. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 5 minutes. The precipitate was washed three times with distilled water and dried in a vacuum drying oven at 80℃ for 12 hours to obtain a full-shell precursor. The full-shell precursor was spread in a crucible and transferred to a high-temperature tube furnace. Oxygen was introduced at a flow rate of 150 mL / min, and the temperature was increased to 650℃ at a rate of 2℃ / min. The temperature was kept constant for 3 hours, and then the temperature was decreased to 25℃ at a rate of 5℃ / min. The product was then removed to obtain a multilayer core-shell nanofunctional unit. Step S5: Weigh out 98 parts by weight of barium titanate powder, 3 parts by weight of calcium zirconate, 0.3 parts by weight of high-entropy pyrochlore nanocrystals, 1.3 parts by weight of multilayer core-shell nanofunctional units, 10 parts by weight of binder, 30 parts by weight of ethanol, and 30 parts by weight of toluene; the barium titanate powder is prepared by hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98; Step S6: Barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, multilayer core-shell nanofunctional units, and binder are sequentially added to a horizontal ball mill jar. Ethanol and toluene are added, and the ball-to-material ratio is 4:1. After sealing the jar, it is placed on a horizontal ball mill and ball-milled at 70 r / min for 30 h. After sieving through a 200-mesh sieve, it is degassed in a vacuum degassing machine for 30 min and injected into a casting machine. The doctor blade gap is adjusted to 125 μm, and casting is performed at a casting speed of 1 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. The film is cut, and nickel internal electrode paste is printed on the surface of the film by screen printing. The layers are stacked and aligned, covered with ceramic protective films on the top and bottom, and then placed in a vacuum-sealed bag and pressed at 70℃ and 30 MPa for 15 min to obtain a multilayer ceramic green body. Step S7: Place the multilayer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under an air atmosphere, heat it to 200℃ at a rate of 0.5℃ / min and hold for 1 hour. Continue heating to 350℃ and hold for 1 hour. Continue heating to 450℃ and hold for 1 hour. Finally, heat it to 600℃ and hold for 2 hours to remove the binder. Cool it down to 25℃ at a rate of 2℃ / min, take out the binder-removed green body, place it on the propeller boat of the atmosphere tunnel furnace, and introduce a weak reducing atmosphere with a flow rate of 750mL / min, which is a mixture of nitrogen and hydrogen in a volume ratio of 97:3 and the oxygen partial pressure is adjusted by bubbling with a 30℃ humidifier. Heat it up to 1185℃ at a rate of 3℃ / min and hold for 3 hours. Switch the atmosphere to a weak oxidizing atmosphere, which is a mixture of nitrogen and oxygen in a volume ratio of 99:1. Cool it down to 900℃ with the furnace and hold for 2 hours for re-oxidation heat treatment. Cool it down to 25℃ with the furnace to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0020] Example 3: This embodiment describes a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, including the following steps: Step S1: Add 4.35g lanthanum nitrate hexahydrate, 4.4g neodymium nitrate hexahydrate, 4.45g samarium nitrate hexahydrate, 4.5g europium nitrate hexahydrate, 4.55g gadolinium nitrate hexahydrate, 2.5g zirconium oxynitrate, and 200mL ultrapure water to a three-necked flask equipped with a stirrer and thermometer. Mix and stir for 30min to obtain a mixed salt solution. Under the assistance of 80kHz ultrasound, spray the mixed salt solution at a rate of 5mL / min into 500mL of ammonia solution at 70℃ and a mass fraction of 28%. Stir at 500r / min to induce explosive co-precipitation. The precipitate was precipitated to form a mixed hydroxide colloid, which was transferred to a high-pressure reactor and statically hydrothermally treated in an oven at 220°C for 36 h to obtain pyrochlore phase nanocrystal nuclei. The nuclei were washed three times each with distilled water and anhydrous ethanol in a centrifuge at 8000 r / min, and then freeze-dried in a vacuum freeze dryer at -50°C for 24 h to obtain precursor powder. The precursor powder was spread evenly in a crucible, placed in a tube furnace, and pure oxygen was introduced at a flow rate of 200 mL / min. The furnace was flash-calcined to 850°C at a rate of 120°C / min, held for 5 min, and then cooled to 25°C to obtain high-entropy pyrochlore nanocrystals. Step S2: Add 100g of barium titanate powder and 1000mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Disperse the powder ultrasonically at 300W and 40kHz for 30min to obtain a suspension. Add 50mL of polydiallyldimethylammonium chloride aqueous solution while stirring at 400r / min. Stir and react in a 25℃ constant temperature water bath for 1h. After the reaction is complete, centrifuge at 8000r / min for 5min, discard the supernatant, wash the precipitate three times with distilled water, add 500mL of deionized water, and mix. The mixture was stirred for 20 min and then transferred to a jacketed glass reactor. 20 mL of a 1 mol / L tetraethyl orthosilicate ethanol solution was added dropwise at a rate of 0.5 mL / min under a 40°C water bath. The pH was adjusted to 9.5 with 2 mol / L ammonia solution. The mixture was stirred at 200 rpm for 5 h and then centrifuged at 8000 rpm for 5 min. The precipitate was washed three times each with distilled water and anhydrous ethanol to obtain the intermediate product. The polydiallyl dimethyl ammonium chloride aqueous solution was manufactured by Merck, catalog number 409030. Step S3: Mix 100g of intermediate product and 500mL of deionized water and sonicate for 15min. Add 7g of magnesium acetate tetrahydrate and 2g of manganese acetate trihydrate. Mix and stir for 30min under constant temperature water bath at 25℃ and ultrasonic assistance. Add 100mL of 0.1mol / L ammonium oxalate aqueous solution dropwise at a rate of 1mL / min under mechanical stirring at 300r / min. Adjust the pH to 6 with 1mol / L acetic acid and continue stirring for 2h. After the reaction is complete, centrifuge at 8000r / min for 5min. Wash the precipitate 3 times with distilled water and dry in a vacuum drying oven at 80℃ for 12h to obtain Mg-Mn oxalate coated precursor. Step S4: Mix 5g of dysprosium nitrate pentahydrate, 5g of holmium nitrate pentahydrate, 3g of aluminum nitrate nonahydrate, and 200mL of anhydrous ethanol and stir for 30min. Add 2.2g of tetraethyl orthosilicate and continue stirring for 30min to obtain the coating solution; add 100g of... The Mg-Mn oxalate-coated precursor and coating solution were mixed and ultrasonically dispersed for 30 min, then transferred to a constant temperature water bath reactor. Under mechanical stirring at 50℃ and 300 r / min, 50 mL of 80% ethanol solution was added dropwise at a rate of 0.3 mL / min. The reaction was stirred for 6 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 5 min. The precipitate was washed three times with distilled water and dried in a vacuum drying oven at 80℃ for 12 h to obtain a full-shell precursor. The full-shell precursor was spread evenly in a crucible and transferred to a high-temperature tube furnace. Oxygen was introduced at a flow rate of 150 mL / min, and the temperature was increased to 650℃ at a rate of 2℃ / min. The mixture was calcined at a constant temperature for 3 h, and then cooled to 25℃ at a rate of 5℃ / min. The resulting multilayer core-shell nanofunctional unit was obtained. Step S5: Weigh out 100 parts by weight of barium titanate powder, 4 parts by weight of calcium zirconate, 0.5 parts by weight of high-entropy pyrochlore nanocrystals, 2 parts by weight of multilayer core-shell nanofunctional units, 12 parts by weight of binder, 35 parts by weight of ethanol and 35 parts by weight of toluene; the barium titanate powder is prepared by hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98; Step S6: Barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, multilayer core-shell nanofunctional units, and binder are sequentially added to a horizontal ball mill jar. Ethanol and toluene are added, and the ball-to-material ratio is 5:1. After sealing the jar, it is placed on a horizontal ball mill and ball-milled at 80 r / min for 36 h. After sieving through a 200-mesh sieve, it is degassed in a vacuum degassing machine for 30 min and injected into a casting machine. The doctor blade gap is adjusted to 200 μm, and casting is performed at a casting speed of 1.5 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. The film is cut, and nickel internal electrode paste is printed on the surface of the film by screen printing. The layers are stacked and aligned, covered with ceramic protective films on the top and bottom, and then placed in a vacuum-sealed bag and pressed at 70℃ and 30 MPa for 15 min to obtain a multilayer ceramic green body. Step S7: Place the multilayer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under an air atmosphere, heat it to 200℃ at a rate of 0.5℃ / min and hold for 1 hour. Continue heating to 350℃ and hold for 1 hour. Continue heating to 450℃ and hold for 1 hour. Finally, heat it to 600℃ and hold for 2 hours to remove the binder. Cool it down to 25℃ at a rate of 2℃ / min, take out the binder-removed green body, place it on the propeller boat of the atmosphere tunnel furnace, and introduce a weak reducing atmosphere with a flow rate of 1000mL / min, which is a mixture of nitrogen and hydrogen in a volume ratio of 97:3 and the oxygen partial pressure is adjusted by bubbling with a 35℃ humidifier. Heat it up to 1220℃ at a rate of 5℃ / min and hold for 4 hours. Switch the atmosphere to a weak oxidizing atmosphere, which is a mixture of nitrogen and oxygen in a volume ratio of 99:1. Cool it down to 900℃ with the furnace and hold for 2 hours for re-oxidation heat treatment. Cool it down to 25℃ with the furnace to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0021] Comparative Example 1: This comparative example illustrates a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, comprising the following steps: Step S1: Weigh out 98 parts of barium titanate powder, 3 parts of calcium zirconate, 10 parts of binder, 30 parts of ethanol, and 30 parts of toluene according to the following weight proportions; the barium titanate powder is prepared by hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98; Step S2: Add barium titanate powder, calcium zirconate, and binder sequentially into a horizontal ball mill jar, add ethanol and toluene, with a ball-to-material ratio of 4:1. After sealing the jar, place it on a horizontal ball mill and ball mill at 70 r / min for 30 h. Sieve through a 200-mesh sieve, degas in a vacuum degassing machine for 30 min, and inject into a casting machine. Adjust the doctor blade gap to 125 μm and cast at a casting speed of 1 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. Cut the film, screen print nickel internal electrode paste on the film surface, stack and align the layers, cover with ceramic protective films on the top and bottom, pack into a vacuum-sealed bag, and press at 70℃ and 30 MPa for 15 min to obtain a multi-layer ceramic green body. Step S3: Place the multilayer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under an air atmosphere, heat it to 200℃ at a rate of 0.5℃ / min and hold for 1 hour. Continue heating to 350℃ and hold for 1 hour. Continue heating to 450℃ and hold for 1 hour. Finally, heat it to 600℃ and hold for 2 hours to remove the binder. Cool it down to 25℃ at a rate of 2℃ / min, take out the binder-removed green body, place it on the propeller boat of the atmosphere tunnel furnace, and introduce a weak reducing atmosphere with a flow rate of 750mL / min, which is a mixture of nitrogen and hydrogen in a volume ratio of 97:3 and the oxygen partial pressure is adjusted by bubbling with a 30℃ humidifier. Heat it up to 1185℃ at a rate of 3℃ / min and hold for 3 hours. Switch the atmosphere to a weak oxidizing atmosphere, which is a mixture of nitrogen and oxygen in a volume ratio of 99:1. Cool it down to 900℃ with the furnace and hold for 2 hours for re-oxidation heat treatment. Cool it down to 25℃ with the furnace to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0022] Comparative Example 2: This comparative example illustrates a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, comprising the following steps: Step S1: Add 4.33g lanthanum nitrate hexahydrate, 4.38g neodymium nitrate hexahydrate, 4.43g samarium nitrate hexahydrate, 4.48g europium nitrate hexahydrate, 4.53g gadolinium nitrate hexahydrate, 2.4g zirconium oxynitrate, and 200mL ultrapure water to a three-necked flask equipped with a stirrer and thermometer. Mix and stir for 30min to obtain a mixed salt solution. Under the assistance of 60kHz ultrasound, spray the mixed salt solution at a rate of 4mL / min into 500mL of ammonia solution at 60℃ and a mass fraction of 27%. Stir at 400r / min to generate explosive co-excitation. Precipitation was generated to form a mixed hydroxide colloid, which was transferred to a high-pressure reactor and statically hydrothermally treated in an oven at 200℃ for 24 h to obtain pyrochlore phase nanocrystal nuclei. The nuclei were washed three times each with distilled water and anhydrous ethanol in a centrifuge at 8000 r / min, and then freeze-dried in a vacuum freeze dryer at -50℃ for 24 h to obtain precursor powder. The precursor powder was spread evenly in a crucible, placed in a tube furnace, and pure oxygen was introduced at a flow rate of 150 mL / min. The furnace was flash-calcined to 800℃ at a rate of 100℃ / min, held for 3 min, and then cooled to 25℃ to obtain high-entropy pyrochlore nanocrystals. Step S2: Weigh out 98 parts by weight of barium titanate powder, 3 parts by weight of calcium zirconate, 0.3 parts by weight of high-entropy pyrochlore nanocrystals, 10 parts by weight of binder, 30 parts by weight of ethanol and 30 parts by weight of toluene; the barium titanate powder is prepared by hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98; Step S3: Add barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, and binder sequentially into a horizontal ball mill jar, add ethanol and toluene, and the ball-to-material ratio is 4:1. After sealing the jar, place it on a horizontal ball mill and ball mill at 70 r / min for 30 h. Sieve through a 200-mesh sieve, degas in a vacuum degassing machine for 30 min, and inject into a casting machine. Adjust the doctor blade gap to 125 μm and cast at a casting speed of 1 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. Cut the film, print nickel internal electrode paste on the film surface by screen printing, stack and align the layers, cover with ceramic protective films on the top and bottom, put into a vacuum sealing bag, and press at 70℃ and 30 MPa for 15 min to obtain a multilayer ceramic green body. Step S4: Place the multilayer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under an air atmosphere, heat it to 200℃ at a rate of 0.5℃ / min and hold for 1 hour. Continue heating to 350℃ and hold for 1 hour. Continue heating to 450℃ and hold for 1 hour. Finally, heat it to 600℃ and hold for 2 hours to remove the binder. Cool it down to 25℃ at a rate of 2℃ / min, take out the binder-removed green body, place it on the propeller boat of the atmosphere tunnel furnace, and introduce a weak reducing atmosphere with a flow rate of 750mL / min, which is a mixture of nitrogen and hydrogen in a volume ratio of 97:3 and the oxygen partial pressure is adjusted by bubbling with a 30℃ humidifier. Heat it up to 1185℃ at a rate of 3℃ / min and hold for 3 hours. Switch the atmosphere to a weak oxidizing atmosphere, which is a mixture of nitrogen and oxygen in a volume ratio of 99:1. Cool it down to 900℃ with the furnace and hold for 2 hours for re-oxidation heat treatment. Cool it down to 25℃ with the furnace to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0023] Comparative Example 3: This comparative example illustrates a method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs, comprising the following steps: Step S1: Add 95g of barium titanate powder and 1000mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Disperse the powder ultrasonically at 300W and 40kHz for 30min to obtain a suspension. Add 45mL of polydiallyldimethylammonium chloride aqueous solution while stirring at 400r / min. Stir and react in a 25℃ constant temperature water bath for 1h. After the reaction is complete, centrifuge at 8000r / min for 5min, discard the supernatant, wash the precipitate three times with distilled water, add 500mL of deionized water, and mix. Stir for 18 min, transfer to a jacketed glass reactor, and add 18 mL of 1 mol / L tetraethyl orthosilicate ethanol solution dropwise at a rate of 0.5 mL / min in a 40°C water bath. Adjust the pH to 9.5 with 2 mol / L ammonia solution, stir the reaction at 200 r / min for 4.5 h, centrifuge at 8000 r / min for 5 min, and wash the precipitate three times each with distilled water and anhydrous ethanol to obtain the intermediate product. The polydiallyl dimethyl ammonium chloride aqueous solution was manufactured by Merck, catalog number 409030. Step S2: Mix 95g of intermediate product and 500mL of deionized water and sonicate for 15min. Add 6.5g of magnesium acetate tetrahydrate and 1.5g of manganese acetate trihydrate. Mix and stir for 30min in a constant temperature water bath at 25℃ with ultrasonic assistance. Add 100mL of 0.1mol / L ammonium oxalate aqueous solution dropwise at a rate of 1mL / min under mechanical stirring at 300r / min. Adjust the pH to 6 with 1mol / L acetic acid and continue stirring for 2h. After the reaction is complete, centrifuge at 8000r / min for 5min. Wash the precipitate three times with distilled water and dry in a vacuum drying oven at 80℃ for 12h to obtain the Mg-Mn oxalate coated precursor. Step S3: Mix 4.5g of dysprosium nitrate pentahydrate, 4.5g of holmium nitrate pentahydrate, 2.5g of aluminum nitrate nonahydrate, and 200mL of anhydrous ethanol and stir for 30min. Add 2.1g of tetraethyl orthosilicate and continue stirring for 30min to obtain the coating solution. Mix 100g of Mg-Mn oxalate-coated precursor and coating solution and ultrasonically disperse for 30min. Transfer to a constant temperature water bath reactor. Under mechanical stirring at 50℃ and 300r / min, add 50mL of a mixture with a mass fraction of [missing value] dropwise at a rate of 0.3mL / min. An 80% ethanol solution was stirred for 6 hours. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 5 minutes. The precipitate was washed three times with distilled water and dried in a vacuum drying oven at 80℃ for 12 hours to obtain a full-shell precursor. The full-shell precursor was spread in a crucible and transferred to a high-temperature tube furnace. Oxygen was introduced at a flow rate of 150 mL / min, and the temperature was increased to 650℃ at a rate of 2℃ / min. The temperature was kept constant for 3 hours, and then the temperature was decreased to 25℃ at a rate of 5℃ / min. The product was then removed to obtain a multilayer core-shell nanofunctional unit. Step S4: Weigh out 98 parts of barium titanate powder, 3 parts of calcium zirconate, 1.3 parts of multilayer core-shell nanofunctional units, 10 parts of binder, 30 parts of ethanol, and 30 parts of toluene according to the following weight proportions; the barium titanate powder is prepared by hydrothermal method; the binder is polyvinyl butyral, model Butvar B-98; Step S5: Barium titanate powder, calcium zirconate, multilayer core-shell nanofunctional units, and binder are sequentially added to a horizontal ball mill jar. Ethanol and toluene are added, and the ball-to-material ratio is 4:1. After sealing the jar, it is placed on a horizontal ball mill and ball-milled at 70 r / min for 30 h. After sieving through a 200-mesh sieve, it is degassed in a vacuum degassing machine for 30 min and then injected into a casting machine. The doctor blade gap is adjusted to 125 μm, and casting is performed at a casting speed of 1 m / min and three-stage hot air drying temperatures of 40℃, 60℃, and 80℃ to obtain a ceramic film. The film is cut, and nickel internal electrode paste is printed on the surface of the film by screen printing. The layers are stacked and aligned, covered with ceramic protective films on the top and bottom, and then placed in a vacuum-sealed bag and pressed at 70℃ and 30 MPa for 15 min to obtain a multilayer ceramic green body. Step S6: Place the multilayer ceramic green body on a firing plate and put it into a box-type resistance furnace. Under an air atmosphere, heat it to 200℃ at a rate of 0.5℃ / min and hold for 1 hour. Continue heating to 350℃ and hold for 1 hour. Continue heating to 450℃ and hold for 1 hour. Finally, heat it to 600℃ and hold for 2 hours to remove the binder. Cool it down to 25℃ at a rate of 2℃ / min, take out the binder-removed green body, place it on the propeller boat of the atmosphere tunnel furnace, and introduce a weak reducing atmosphere with a flow rate of 750mL / min, which is a mixture of nitrogen and hydrogen in a volume ratio of 97:3 and the oxygen partial pressure is adjusted by bubbling with a 30℃ humidifier. Heat it up to 1185℃ at a rate of 3℃ / min and hold for 3 hours. Switch the atmosphere to a weak oxidizing atmosphere, which is a mixture of nitrogen and oxygen in a volume ratio of 99:1. Cool it down to 900℃ with the furnace and hold for 2 hours for re-oxidation heat treatment. Cool it down to 25℃ with the furnace to obtain a fine-grained dielectric material for high-pressure, high-reliability MLCCs.
[0024] The fine-grained dielectric materials for high-voltage, high-reliability MLCCs prepared in Examples 1-3 and Comparative Examples 1-3 were polished on both sides using 2000-grit sandpaper, and then silver electrodes were uniformly plated on both sides to obtain samples. The samples were immersed in insulating oil to prevent surface arcing, and a continuous voltage increase method was used until breakdown. The breakdown voltage and sample thickness were recorded, and the breakdown field strength was calculated. At three temperature points of 25℃, 150℃, and 200℃, a DC voltage of 500V was applied to the samples for 1 minute, and the insulation resistance value was read and converted to resistivity. The samples were placed in a high-temperature oven at 200℃, and a DC bias voltage of 3 times the rated operating voltage was continuously applied. The insulation resistance was measured every 30 minutes at the moment of power failure, and the failure criterion was a decrease of one order of magnitude in insulation resistance relative to the initial value. The duration was recorded. Under a test signal of 1kHz and 1Vrms, with the capacitance value at 25℃ as a reference, the capacitance change rate during the process of heating from -55℃ to 150℃ was measured. The test results are shown in the table. Comparing Examples 1-3 with Comparative Examples 1-3: In Example 1, the addition amount of high-entropy pyrochlore nanocrystals and multilayer core-shell nanofunctional units was the lowest, and the flash calcination temperature and sintering temperature were both at a relatively mild level. This resulted in weak static pinning at the grain boundaries, insufficient phase densification and acceptor doping concentration provided by the multilayer core-shell units, poor grain refinement, uniformity of grain boundary potential, and poor oxygen vacancy trapping ability, leading to the lowest breakdown tolerance and high-temperature aging lifetime. In Example 2, the amount of high-entropy pyrochlore nanocrystals and multilayer core-shell nanofunctional units was moderate, while the flash calcination temperature and sintering temperature were increased. The lattice distortion pinning effect synergistically with the gradient functional release of multilayer core-shell units results in a complete grain boundary network and increased barrier height, leading to relatively moderate overall performance. In Example 3, the high-entropy pyrochlore nanocrystals and multilayer core-shell nanofunctional units are most abundant, resulting in the smallest grain size, higher grain boundary barriers, and trapped and frozen oxygen vacancies, leading to the best breakdown field strength, high-temperature insulation resistivity, and aging life. Comparing Example 2 with Comparative Example 1, it can be seen that Comparative Example 1 is a pure barium titanate system, lacking grain boundary pinning phase and acceptor doping. During sintering, grain boundary migration is unimpeded, and severe abnormal grain growth occurs, resulting in a lower number of effective grain boundaries per unit thickness. The high concentration of oxygen vacancies within the grains, coupled with the lack of acceptor compensation, leads to extensive long-range transport of oxygen vacancies along grain boundaries under high temperature and high electric field conditions, resulting in significant leakage current pathways and thus poor performance. Comparing Example 2 with Comparative Example 2 reveals that Comparative Example 2 only introduced high-entropy pyrochlore nanocrystals as a static pinning phase, suppressing excessive grain growth. However, due to the lack of multi-layered core-shell nanofunctional units, there was no transient liquid phase-assisted densification provided by the outer rare-earth silicate layer during sintering, resulting in numerous residual pores and defects within the ceramic body. Furthermore, the uneven dispersion of the acceptor dopant elements, introduced through traditional mechanical mixing, resulted in high grain boundary barriers. The unevenness of the low-density, defective and barrier-inhomogeneous structures become rapid channels for oxygen vacancy migration, resulting in a lower aging life than Example 2. Comparing Example 2 with Comparative Example 3, it can be seen that Comparative Example 3 only relies on multilayer core-shell nanofunctional units to achieve uniform doping and time-sequential liquid-phase densification, which improves both grain refinement and room-temperature insulation performance. However, it lacks high-entropy pyrochlore nanocrystals. Under extreme coupling conditions of high temperature and strong electric field, the grain boundary pinning phase composed of ordinary acceptor ions in the multilayer core-shell units undergoes thermal activation and depinning, and oxygen vacancies regain long-range migration ability, leading to continuous deterioration of insulation resistance over time until failure, resulting in a lower aging life.
[0025] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0026] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A fine-grained dielectric material for high-voltage, high-reliability MLCCs, characterized in that, Includes the following components by weight: 95-100 parts of barium titanate powder, 2-4 parts of calcium zirconate, 0.1-0.5 parts of high-entropy pyrochlore nanocrystals, 0.5-2 parts of multilayer core-shell nanofunctional units, and 8-12 parts of binder; The high-entropy pyrochlore nanocrystals are prepared by the following steps: Lanthanum nitrate hexahydrate, neodymium nitrate hexahydrate, samarium nitrate hexahydrate, europium nitrate hexahydrate, gadolinium nitrate hexahydrate, zirconium oxynitrate, and ultrapure water were mixed, sprayed into an ammonia solution, stirred, and subjected to static hydrothermal treatment to obtain pyrochlore phase nanocrystal nuclei. The nuclei were washed, freeze-dried, flash-calcined in a tube furnace, and cooled to obtain high-entropy pyrochlore nanocrystals.
2. The fine-grained dielectric material for high-voltage, high-reliability MLCCs according to claim 1, characterized in that, The barium titanate powder was prepared by a hydrothermal method; the binder was polyvinyl butyral, model Butvar B-98.
3. The fine-grained dielectric material for high-voltage, high-reliability MLCCs according to claim 1, characterized in that, The ratio of the amounts of lanthanum nitrate hexahydrate, neodymium nitrate hexahydrate, samarium nitrate hexahydrate, europium nitrate hexahydrate, gadolinium nitrate hexahydrate, zirconium oxynitrate, ultrapure water, and ammonia solution is 4.3-4.35g: 4.35-4.4g: 4.4-4.45g: 4.45-4.5g: 4.5-4.55g: 2.3-2.5g: 200mL: 500mL; the mass fraction of the ammonia solution is 25-28%.
4. The fine-grained dielectric material for high-voltage, high-reliability MLCCs according to claim 1, characterized in that, The multilayer core-shell nanofunctional unit is prepared by the following steps: Step b1: Disperse barium titanate powder and the first portion of deionized water by ultrasonication, add polydiallyldimethylammonium chloride aqueous solution and stir to adsorb the reaction, centrifuge, discard the supernatant, wash the precipitate, add the second portion of deionized water and mix, add tetraethyl orthosilicate ethanol solution dropwise under water bath, adjust the pH with ammonia water, stir to react, centrifuge, wash the precipitate to obtain the intermediate product; Step b2: Mix the intermediate product and deionized water with sonication, add magnesium acetate tetrahydrate and manganese acetate trihydrate, add ammonium oxalate aqueous solution, adjust the pH with acetic acid, stir the reaction, centrifuge, wash the precipitate, and dry to obtain Mg-Mn oxalate coated precursor. Step b3: Mix dysprosium nitrate pentahydrate, holmium nitrate pentahydrate, aluminum nitrate nonahydrate and anhydrous ethanol, add tetraethyl orthosilicate and stir to obtain a coating solution; The Mg-Mn oxalate-coated precursor and coating solution were mixed and sonicated, then added dropwise to the hydrolysate, stirred and reacted, centrifuged, washed and dried to obtain a full-shell precursor; the full-shell precursor was transferred to a high-temperature tube furnace for calcination and cooling to obtain multilayer core-shell nanofunctional units.
5. The fine-grained dielectric material for high-voltage, high-reliability MLCCs according to claim 4, characterized in that, In step b1, the ratio of barium titanate powder, total deionized water, polydiallyl dimethyl ammonium chloride aqueous solution, and tetraethyl orthosilicate ethanol solution is 90-100g:1500mL:40-50mL:15-20mL; the barium titanate powder is prepared by a hydrothermal method; the first part of deionized water accounts for 2 / 3 of the total deionized water; the second part of deionized water accounts for 1 / 3 of the total deionized water; the polydiallyl dimethyl ammonium chloride aqueous solution is manufactured by Merck, catalog number 409030; the concentration of the tetraethyl orthosilicate ethanol solution is 1mol / L; and the concentration of the ammonia water is 2mol / L.
6. The fine-grained dielectric material for high-voltage, high-reliability MLCCs according to claim 4, characterized in that, In step b2, the ratio of the intermediate product, deionized water, magnesium acetate tetrahydrate, manganese acetate trihydrate, and ammonium oxalate aqueous solution is 90-100g: 500mL: 6-7g: 1-2g: 100mL; the concentration of the ammonium oxalate aqueous solution is 0.1mol / L; and the concentration of the acetic acid is 1mol / L.
7. The fine-grained dielectric material for high-voltage, high-reliability MLCCs according to claim 4, characterized in that, In step b3, the ratio of dysprosium nitrate pentahydrate, holmium nitrate pentahydrate, aluminum nitrate nonahydrate, anhydrous ethanol, tetraethyl orthosilicate, Mg-Mn oxalate-coated precursor, and hydrolysate is 4-5g:4-5g:2-3g:200mL:2-2.2g:100g:50mL; the hydrolysate is an 80% ethanol solution.
8. A method for preparing a fine-grained dielectric material for high-voltage, high-reliability MLCCs as described in any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Weigh out 95-100 parts of barium titanate powder, 2-4 parts of calcium zirconate, 0.1-0.5 parts of high-entropy pyrochlore nanocrystals, 0.5-2 parts of multilayer core-shell nanofunctional units, 8-12 parts of binder, 25-35 parts of ethanol, and 25-35 parts of toluene according to the following weight proportions. Step 2: Add barium titanate powder, calcium zirconate, high-entropy pyrochlore nanocrystals, multilayer core-shell nanofunctional units and binder to a ball mill jar, add ethanol and toluene, ball mill, sieve, degas, inject into a casting machine to form a ceramic film, cut, and screen print nickel internal electrode paste on the surface of the film, stack and align the layers, cover with ceramic protective films on the top and bottom, press, and obtain a multilayer ceramic green body; Step 3: Remove the binder from the multilayer ceramic green body, cool it down, place it on the propeller boat of the atmosphere tunnel furnace, sinter it, then perform oxidation heat treatment, and cool it down to obtain fine-grained dielectric material for high-pressure, high-reliability MLCCs.
